A novel approach for estimating the magnetization curve of magnetic fluids. Issue 6 (7th August 2017) - Szczech, Marcin
Abstract : Purpose: Magnetization is one of the most important parameters of magnetic fluids. The shape of the magnetization curve often determines the application of a fluid in a device. On the basis of the magnetization curve, it is also possible to estimate, for example, the distribution and size of the particles in a magnetic fluid carrier fluid. The aim of this paper is to present a new approach for estimating the magnetization curve. Design/methodology/approach: The proposed method is an iterative method based on the measurement of magnetic induction on a test stand. To determine the magnetization curve, a numerical simulation of the magnetic field distributions for the preliminary magnetization curve should also be performed. Numerical simulations for modified forms of the magnetization curve are performed until the difference between the results obtained by the measurement and numerical simulation are the smallest. Findings: This paper presents the results of magnetization curve research for ferrofluids and magnetorheological fluids. Originality/value: The discussed method shows the possibilities of using numerical simulations of magnetic field distribution to determine the magnetic properties of magnetic fluids. This method may be an alternative for estimating the magnetization curve of the magnetic fluid compared to other methods.